Prevalence, severity, frequency and healthcare resource use of epilepsy among individuals with Rett Syndrome: analysis of data from a Rett Center of Excellence - Rashid, Nazia; Ruetsch, Charles; LaFrance, Emily M.; Darer, Jonathan D. (Frontiers in Neurology, 2025)
BackgroundIndividuals with Rett Syndrome (RTT) frequently experience comorbid epilepsy. Few studies have examined the impact of epilepsy healthcare utilization using real-world datasets among RTT. The objective of this study was to examine all-cause and epilepsy-related healthcare utilization among individuals with RTT using electronic health record (EHR) data and chart notes.MethodsA retrospective comparative cohort analysis was performed among RTT individuals with and without epilepsy using EHR structured and abstracted clinical notes data. Epilepsy cases were stratified into severe (associated with prolonged or intractable seizures) and non-severe. RTT individuals with no epilepsy, non-severe epilepsy, and severe epilepsy were compared on seizure frequency and healthcare utilization.ResultsIn this analysis, 98 individuals with RTT were included: 71 (72%) had epilepsy of which 33 (46%) had severe epilepsy. Individuals with severe epilepsy (n = 33) vs. non-severe epilepsy [experienced daily seizures (53.8% vs. 11.1%), weekly (23.1% vs. 14.8%), or monthly (23.1% vs. 22.2%)], respectively; however, more than half (51.9%) experienced no seizures among the non-severe group. The prevalence of ED visits was significantly higher among those with severe epilepsy compared to those with non-severe epilepsy (27% vs. 7%, p < 0.05). Inpatient admissions were significantly more prevalent among those with severe epilepsy vs. non-severe epilepsy (37% vs. 14%, p < 0.05).ConclusionsRates of epilepsy among individuals with RTT are at increased risk for healthcare utilization, especially those with severe epilepsy described as prolonged or intractable seizures. Of individuals with epilepsy, up to one-fourth experience daily seizures. It is important to educate health professionals of the high rate of concomitant epilepsy among RTT syndrome and how it can represent a substantial burden to patients and families with RTT. The frequency of seizures is more common among those with severe epilepsy.